Pengaruh Tipe Sistem Hidroponik dan Ukuran Wadah Nutrisi Terhadap Hasil Buah Tomat Ceri (Lycopersicum esculentum M.) - Disca Anggi Pratiwi; Sugeng Triyono; Winda Rahmawati; Agus Haryanto (abe.fp.unila.ac.id, 2023)
Cherry tomatoes (Lycopersicum esculentum M.) are a type of tomato that many people like because they taste sweet and are rich in vitamins. However, conventionally cherry tomatoes have not been widely cultivated in Indonesia because besides of susceptible to disease, cultivation techniques in open fields are not well understood by many farmers either. This research aims to determine the appropriate size of the nutrient jar and hydroponic system. The experiment used a completely randomized design (CRD) which was arranged factorially with three replications. The first factor is the size of the nutrition jar which consists of 3 levels, namely 500 mL (P1), 1500 mL (P2), and 2500 mL (P3). The second factor was the type of hydroponic system consisting of Wick System (HW), Dry System (HD), and Floating System (HF). The results showed that the nutrient jar size had a positive effect on evapotranspiration, number of leaves, root length, number of flowers, fruit weight, and water content of the fruit. The hydroponic system significantly affected the number of flowers, root length, fruit weight, and in general the Wick System (HW) had better performance compared to the Dry system (HD) and the Floating system (HF). The interaction of the two treatment factors was not significant. The data showed that the 1500mL Wick System (P2HW) was the most optimum treatment, based on the parameters of evapotranspiration/consumption of nutrient (2.6-3 liters), number of leaves 17 leaves), root length (23.4-25.1 cm), and fruit weight (14.1-15.22 grams) as well. Keyword : Cherry tomatoes (Lycopersicum esculentum M.), hydroponic, nutrient jar size. wick system